Lgbtphobia and mental health: The impact of prejudice and discrimination from a cognitive-behavioral Perspective (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
This study aimed to comprehend the impact of LGBTphobia on mental health through the lens of Cognitive-Behavioral Therapy (CBT), focusing on cognitive processing. Additionally, we explored the significance of LGBTQIA+ shelters in mitigating the damages caused by prejudice and discrimination. Individual interviews, conducted in an online format alongside semi-structured questionnaires, were employed for data collection. The research involved five participants from a LGBTQIA+ shelter in Manaus, Amazonas. Findings revealed that an environment permeated by LGBTphobia contributes to the development of cognitive distortions and emotional destabilization. In this context, shelters not only provide refuge but also facilitate actions conducive to social integration, psychological damage containment, and the development of new life perspectives. Furthermore, the study emphasizes the necessity of strengthening these initiatives and expanding psychological intervention possibilities to meet the needs of both users and multidisciplinary teams.
Keywords: LGBTQIA+; Violence; Cognitive Distortions; Cognitive-Behavioral Therapy